Look out captain, I hear an ambiguous alien! A study of interpretation bias and anxiety in young children. (October 2019) - Stuijfzand, Suzannah; Chakrabarti, Bhismadev; Reynolds, Shirley; Dodd, Helen F.
Abstract: There is convincing evidence that anxious children and adolescents are biased to interpret ambiguity in a negative way (Stuijfzand, Creswell, Field, Pearcey, & Dodd, 2017). However, little research examines interpretation bias in children under eight years. This is due to existing measures of interpretation bias being inappropriate for young children. Consequently, we aimed to develop a new interpretation bias task for young children using tones. Children learnt to associate high tones with a 'happy alien' and low tones with an 'angry alien'. They were then asked to classify tones from the middle of the frequency range (ambiguous tones) as 'happy' or 'angry'. Corrugator muscle activity was recorded alongside behavioural responses. A community sample of 110 children aged 4–8 years, split into high and low anxious groups, completed the task. High anxious children were more likely to interpret the ambiguous tones as negative but this effect was small and only apparent after controlling for developmental factors. Corrugator activity aligned with behavioural responses for trained but not ambiguous tones. This is the first study to assess interpretation bias in young children using behavioural and physiological measures. Results indicate the task is developmentally appropriate and has potential utility for future research. Highlights: The new interpretation bias task for young children is developmentally appropriate. Children high in anxiety were more likely to classify ambiguous tones as negative. This relationship was only clear when developmental factors were controlled for. Corrugator activity matched valence judgements for tones with clear valence. Corrugator activity did not match valence judgements of ambiguous tones.